Online group psychodynamic psychotherapy—The effectiveness and role of attachment—The results of a short study - Wajda, Zbigniew; Kapinos-Gorczyca, Agnieszka; Lizińczyk, Sebastian; Sitnik-Warchulska, Katarzyna; Izydorczyk, Bernadetta (Frontiers in Psychiatry, 2022)
The role of remote treatment, including psychotherapy, has increased during the COVID-19 pandemic. The results of research in this area are promising, initially pointing to similar effectiveness for online psychotherapy as that of face-to-face psychotherapy. A significantly smaller amount of research has been conducted on online group psychotherapy, in particular, in the psychodynamic paradigm. Many authors have drawn attention to the need to conduct further research, considering specific patient features, for example, personality traits, attachment style, age, and other demographic variables. This study conducted pre- and post-treatment (10 weeks) and a 6-week follow-up, on the effectiveness of online synchronous group psychodynamic psychotherapy (via Zoom) taking into account patients’ attachment styles. Four main hypotheses were tested: H1: Patients will obtain a lower score in the attachment’s dimensions of anxiety and avoidance; H2: Patients will get a lower level of symptoms and sense of loneliness; H3: Patients will have increased self-esteem; and H4: The anxiety and avoidance dimensions of the attachment will be predictors for the effectiveness of online psychodynamic group psychotherapy. Twenty-two outpatients participated in the study, out of which 18 suffered from neurotic, stress-related, and somatoform disorders (F40-F48), and four suffered from a depressive episode (F32.0, F32.1) according to ICD-10. The results of the pre-treatment test showed a reduction in the global severity of psychiatric symptoms (d = −0.526) and depressive symptoms (d = −0.5), as well as an increase in self-esteem (d = 0.444) and feelings of loneliness (d = 0.46). A change in the attachment dimension, anxiety (d = −0.557) and avoidance (d = −0.526), was also observed. The above results were maintained in the follow-up test conducted after 6 weeks. Additionally, a reduction in the symptoms of social phobia was observed. Attachment dimensions were not a predictor of the effectiveness of psychotherapy, but a decrease in avoidance during therapy was a predictor of increased symptoms of pain. The results of the research are promising in terms of psychiatric symptoms and increased self-esteem. During therapy, there may be a favorable change in attachment dimensions, but this variable was not shown to be a predictor of results. These results suggest that more controlled research is required.